2017
DOI: 10.1016/j.jmb.2016.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Contributions of Tryptophan Residues within the Dimerization Domain to Nanog Function

Abstract: The level of the transcription factor Nanog directly determines the efficiency of mouse embryonic stem cell self-renewal. Nanog protein exists as a dimer with the dimerization domain composed of a simple repeat region in which every fifth residue is a tryptophan, the tryptophan repeat (WR). Although WR is necessary to enable Nanog to confer LIF-independent self-renewal, the mechanism of dimerization and the effect of modulating dimerization strength have been unclear. Here we couple mutagenesis with functional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
2

Relationship

4
4

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 25 publications
2
20
0
Order By: Relevance
“…In contrast, when a GFP-Nanog fusion in which the tryptophan residues in the tryptophan repeat (WR; Nanog-W10A) was expressed in CHO cells alongside (FLAG)3-Nanog, incubation of nuclear lysate with anti-FLAGconjugated beads yielded no fluorescence ( Fig 1B). This is consistent with previous reports of a critical role for WR tryptophan residues in homodimerisation of Nanog (Mullin, Yates et al 2008, Wang, Levasseur et al 2008, Mullin, Gagliardi et al 2017). In addition, incubation of beads with (FLAG)3-Nanog and GFP-Sox2, resulted in localisation of fluorescence to the bead surface ( Fig 1B).…”
Section: Nanog Forms Homo-multimers and Binds To Sox2 And Oct4 In Chosupporting
confidence: 94%
See 1 more Smart Citation
“…In contrast, when a GFP-Nanog fusion in which the tryptophan residues in the tryptophan repeat (WR; Nanog-W10A) was expressed in CHO cells alongside (FLAG)3-Nanog, incubation of nuclear lysate with anti-FLAGconjugated beads yielded no fluorescence ( Fig 1B). This is consistent with previous reports of a critical role for WR tryptophan residues in homodimerisation of Nanog (Mullin, Yates et al 2008, Wang, Levasseur et al 2008, Mullin, Gagliardi et al 2017). In addition, incubation of beads with (FLAG)3-Nanog and GFP-Sox2, resulted in localisation of fluorescence to the bead surface ( Fig 1B).…”
Section: Nanog Forms Homo-multimers and Binds To Sox2 And Oct4 In Chosupporting
confidence: 94%
“…The dimerisation of Nanog may also be affected by additional Nanog partner proteins. While the residues involved in Nanog homodimerisation and heterodimerisation with Sox2 have been determined (Mullin, Yates et al 2008, Gagliardi, Mullin et al 2013, Mullin, Gagliardi et al 2017, how Nanog interacts with additional partners remains to be shown. For example, while Nanog has been reported to bind Oct4 (Wang, Levasseur et al 2008), other studies did not report an interaction between Nanog and Oct4 (van den Berg, Snoek et al 2010, Gagliardi, Mullin et al 2013.…”
Section: Introductionmentioning
confidence: 99%
“…In order to further dissect the PIP domain of PALI1 and PALI2, we closely analyzed the conservation and charges of its constituent amino acids ( Figure 3C). Two highly conserved tryptophans (W1125 and W1186) were selected for mutation due to the potential importance of aromatic residues in protein-protein interactions and for structural stability within a modular domain (Mullin et al, 2017). Mutagenesis of these tryptophans to alanines individually did not disrupt the interaction with EZH2 ( Figure 3D).…”
Section: Pali1 Is a Member Of A Vertebrate-specific Family Of Prc21 mentioning
confidence: 99%
“…Alanine substitution mutagenesis identified aromatic and hydrophobic residues that mediate the interaction between TET1 and NANOG. In NANOG, tryptophans within the WR are critical for the biological function of NANOG and mediate NANOG homodimerization and binding to SOX2 aromatic residues [49,50,30,51]. Tryptophan residues within the NANOG WR also interact with aromatic residues in the TET1 C-terminus, suggesting an interaction by aromatic stacking.…”
Section: Tet1mentioning
confidence: 99%